In: Computer Science
in assembly show output too - thanks
. Translate the following expression to Assembly:
a. 5 x (10 + 13)
b. 5 - 4 x 4
c. AX = FF50h - ABCDh
d. EAX = (EBX - 4) x (-1)
e. EAX = 0
EBX = 9
ECX = 10
X = EAX x EBX - ECX
Explanation:-
So in this way we can convert an expression into assembly language using the above instruction.The output for each expression is
1)115
2)-11
3)5383
4) (EBX - 4) x (-1)
5)-10
Note:-The explanation of each output is being provided above
############################################################################################
So in case of any doubt do ask in the comment section...Hope you will like it